Pelatihan Pemanfaatan Aplikasi Wizer.me sebagai Penunjang Bahan Ajar Terdiferensiasi untuk Meningkatkan Keterampilan Guru - Yusri, Radhya; Delyana, Hafizah; Melisa, Melisa; Aprilianto, Fadli; Nasyatul A, Restu (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Technology integration in education has become essential to support inclusive and adaptive learning. However, many teachers still face challenges in developing differentiated teaching materials that address their students' diverse learning styles and abilities. This issue stems from teachers' limited knowledge and skills in effectively utilizing innovative technology. This training program aims to enhance the skills of teachers at SMP Negeri 26 Padang in creating differentiated teaching materials through the use of the Wizer.me application. The method employed is a participatory approach consisting of three main phases: training planning, implementation (including theoretical sessions and interactive practice using Wizer.me), and evaluation. The results indicate that the training successfully equipped teachers with strong competencies in operating the Wizer.me application. The program significantly impacted teachers' understanding and skills in utilizing the platform to produce interactive, varied, and student-centered teaching materials. Additionally, participants expressed a high level of satisfaction with the program. Thus, this training program has made a tangible contribution to empowering teachers to leverage technology in creating innovative educational content.